Whole-exome sequencing and digital PCR identified a novel compound heterozygous mutation in the NPHP1 gene in a case of Joubert syndrome and related disorders - Shingo Koyama; Hidenori Sato; Manabu Wada; Toru Kawanami; Mitsuru Emi; Takeo Kato (BMC, 2017)
Abstract Background Joubert syndrome and related disorders (JSRD) is a clinically and genetically heterogeneous condition with autosomal recessive or X-linked inheritance, which share a distinctive neuroradiological hallmark, the so-called molar tooth sign. JSRD is classified into six clinical subtypes based on associated variable multiorgan involvement. To date, 21 causative genes have been identified in JSRD, which makes genetic diagnosis difficult. Case presentation We report here a case of a 28-year-old Japanese woman diagnosed with JS with oculorenal defects with a novel compound heterozygous mutation (p.Ser219*/deletion) in the NPHP1 gene. Whole-exome sequencing (WES) of the patient identified the novel nonsense mutation in an apparently homozygous state. However, it was absent in her mother and heterozygous in her father. A read depth-based copy number variation (CNV) detection algorithm using WES data of the family predicted a large heterozygous deletion mutation in the patient and her mother, which was validated by digital polymerase chain reaction, indicating that the patient was compound heterozygous for the paternal nonsense mutation and the maternal deletion mutation spanning the site of the single nucleotide change. Conclusion It should be noted that analytical pipelines that focus purely on sequence information cannot distinguish homozygosity from hemizygosity because of its inability to detect large deletions. The ability to detect CNVs in addition to single nucleotide variants and small insertion/deletions makes WES an attractive diagnostic tool for genetically heterogeneous disorders.